2013
DOI: 10.1155/2013/698031
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and Zinc Removal from Acid Mine Drainage: Roles of Sludge Surface Area and Neutralising Agents

Abstract: During acid mine drainage (AMD) treatment by alkaline reagent neutralisation, Ni and Zn are partially removed via sorption to Fe and Al hydroxide precipitates. This research evaluated the effect of surface area of precipitates, formed by neutralisation of AMD using three alkalinity reagents (NaOH, Ca(OH) 2 , and CaCO 3 ), on the sorption of Ni and Zn. The BET surface area of the precipitates formed by neutralisation of AMD with NaOH (173.7 m 2 g −1 ) and Ca(OH) 2 (168.2 m 2 g −1 ) was an order of magnitude gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…West Coast AMD is characterised by high acidity and elevated metal concentrations (Fe, Al, Ni, Zn, Cu, Pb, Cd, etc. ) (Olds et al 2013). The sulphur and pyrite content (and therefore AMD generating potential) of coal measures rock varies significantly on a geographic basis within the Buller Coalfield and is also constrained lithologically (Hughes et al 2006;Weber et al 2008;Weisener & Weber 2010).…”
Section: Introductionmentioning
confidence: 99%
“…West Coast AMD is characterised by high acidity and elevated metal concentrations (Fe, Al, Ni, Zn, Cu, Pb, Cd, etc. ) (Olds et al 2013). The sulphur and pyrite content (and therefore AMD generating potential) of coal measures rock varies significantly on a geographic basis within the Buller Coalfield and is also constrained lithologically (Hughes et al 2006;Weber et al 2008;Weisener & Weber 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The Ni concentration was reduced by 26% to an average pre-treated concentration of 0.46 mg/L. The sorption and co-precipitation of Ni with the solid phase of Fe and Al precipitants may be associated with the reduction in Ni concentration as shown in the findings by Olds et al (2013), where a linear trend between pH increase and Ni co-precipitation was observed [28]. The SO 4 2− concentration was reduced by 13% from 1642 mg/L to an average concentration of 1446 mg/L (refer to Figure 4C).…”
Section: Acid Mine Drainage Pre-treatmentmentioning
confidence: 67%
“…Limestone shows a complete removal of iron and aluminum. The formation of iron and aluminum precipitates serve to be beneficial in the partial removal of Ni from AMD 24 . However, the high amount of Fe present in the AMD allowed the near complete removal of Ni from the effluent at most 99.33%.…”
Section: Resultsmentioning
confidence: 99%